Civil service organization as a political determinant of health: analyzing relationships between merit-based hiring, corruption, and population health - Patterson, Andrew C. (My University, 2024)
A growing literature finds that the way governments are organized can impact the societies they serve in important ways. The same is apparent with respect to civil service organizations. Numerous studies show that the recruitment of civil servants based on their credentials rather than on nepotism or patronage reduces corruption in government. Political corruption in turn appears to harm population health. Up to this time, however, civil service organization is not a recognized determinant of health and is little discussed outside of political science disciplines. To provoke a broader conversation on this subject, the following study proposes that meritocratic recruitment of civil servants improves population health. To test this proposition, a series of regression models examines comparative data for 118 countries. Consistent with study hypotheses, meritocratic recruitment of civil servants corresponds longitudinally with both lower rates of corruption and lower rates of infant mortality. Results are similar after robustness checks. Findings with regard to life expectancy are more mixed. However, additional tests suggest meritocratic recruitment contributes to life expectancy over a longer span of time. Findings also offer more support for a direct pathway from meritocratic recruitment to population health rather than via changes in corruption levels per se, although this may depend on a country's level of economic development. Overall, this study offers first evidence that civil service organization, particularly the recruitment of civil servants based on the merits of their applications rather than on whom they happen to know in government, is a positive determinant of health. More research in this area is needed.
Keywords: civil service organization; meritocratic recruitment; political corruption; public administration; population health; comparative analysis; life expectancy; infant mortality